Penerjemahan Frasa Nomina Bahasa Korea ke Bahasa Indonesia dari Buku Esai Naneun Naro Salgiro Haetda ke dalam Hidup Apa Adanya: Kesalahan dan Strategi - Rohmatulloh, Roro 'Ayniy; Young, Hwang Who (Universitas Gadjah Mada, 2024)
The purposes of this research are to identify and analyze noun phrase’s translation errors and translation strategies from Korean to Indonesian that happened in an essay book titled Hidup Apa Adanya (2020), the Indonesian translation of Naneun Naro Salgiro Haetda (나는 나로 살기로 했다) (2016) by Suhyun Kim. This research is done using a descriptive-qualitative analysis method and two theories which are Translation Criticism (1988) by Peter Newmark and Translation Strategies (2016) by Zuchridin Suryawinata and Sugeng Hariyanto. The result indicates that firstly, there are six types of translation errors, which are (1) semantic error as the most found type, (2) omission, (3) word’s class and form’s change, (4) diction error, (5) word by word translation, and (6) cultural terms error. Secondly, there are nine strategies combinations such as (1) expansion and recognized translation, (2) synonymy and transposition, the most used combination, (3) synonymy, transposition, and addition, (4) synonymy, transposition, and borrowing, (5) modulation, transposition, and subtraction, (6) modulation, componential analysis, and addition, (7) borrowing and addition, (8) borrowing and transposition, and (9) borrowing, transposition, reduction, and expansion. The result also shows that the translator did not use cultural equivalent and descriptive equivalent strategies.